Thyroid abscess secondary to infected synovial sarcoma of the thyroid: A case report - Mior Hamzah, Mior Shukri; Chen, Chan Ai; Periasammy, Dineshwary; Ismail, Mazita (Indian Journal of Case Reports, 2025)
Primary sarcomas of the thyroid are very rare, accounting for